2018
DOI: 10.1177/0020872817746224
|View full text |Cite
|
Sign up to set email alerts
|

Community reconstruction orientation by victims of the disaster of a post-monsoon flood in Malaysia

Abstract: A monsoon flood often happens on a huge scale on the East Coast of Peninsular Malaysia and has an immediate impact on the community. This article explores the community reconstruction orientation of the victims of the disaster of a post-monsoon flood in Malaysia. The study was carried out using an exploratory case study design on nine flood victims in Pahang, Malaysia. These informants were chosen by using purposive sampling, and data were gathered using the interview and observation methods. This study found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the disaster risk management category, Amir Zal (2017) analysed the process of rebuilding a community after a monsoon flood in Malaysia through an experimental case study with victims of the disaster and observations in shelters created after the disaster. Charoenkalunyuta et al (2011) evaluate the resilience of land properties for communities affected by disasters arising from natural risks, presenting highlighting the indicators related to the responsibilities of those involved in decision making, provision of data and information and participation of the parties in disaster prevention actions.…”
Section: Performance Criteria In Hos From the Beneficiary Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…In the disaster risk management category, Amir Zal (2017) analysed the process of rebuilding a community after a monsoon flood in Malaysia through an experimental case study with victims of the disaster and observations in shelters created after the disaster. Charoenkalunyuta et al (2011) evaluate the resilience of land properties for communities affected by disasters arising from natural risks, presenting highlighting the indicators related to the responsibilities of those involved in decision making, provision of data and information and participation of the parties in disaster prevention actions.…”
Section: Performance Criteria In Hos From the Beneficiary Perspectivementioning
confidence: 99%
“…Additionally, when analysing the reconstruction process of the community affected by the disaster, Amir Zal (2017) indicated that self-orientation is one of the forms of reconstruction, and this is related to actions that prioritize reconstruction activities, such as actions for health recovery, cleaning and site sanitation. Piyasil et al (2014) analysed the quality of life of children and young people after the 2004 Thailand earthquake.…”
Section: Performance Criteria In Hos From the Beneficiary Perspectivementioning
confidence: 99%
See 2 more Smart Citations